PENGEMBANGAN MATERI AJAR TEKS RESENSI BERBANTUAN MEDIA VLOGNOW PADA SISWA KELAS XI SMA METHODIST-12 MEDAN - Perdana Manurung (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research aims to develop teaching materials for review texts assisted by VlogNow media for class XI SMA. This teaching material is expected to help students in following the learning process in class. This research is a development research (RnD) that uses Borg and Gall research procedures. The product developed from this research is teaching material for review texts in the form of learning videos assisted by VlogNow media for grade XI SMA. The subjects of this development research include material expert validators, media expert validators, subject teachers, and students of grade XI of Methodist-12 Medan Private High School. The data collection techniques used were the distribution of needs analysis questionnaires, structured interviews with subject teachers, and feasibility validation of the products developed. The research instruments used were student needs analysis questionnaire, material expert validation, media expert validation, and subject teacher validation. The results of this study indicate that the products developed are already in very good qualifications with a value from the material expert validator of 92%, media expert validator of 83%, and subject teacher of 88%. An average score of 88% was obtained, so it can be concluded that the product in this study is very suitable for use by students in learning.